Control of Neuronal Migration and Aggregation by Reelin Signaling in the Developing Cerebral Cortex - Hirota, Yuki; Nakajima, Kazunori (Frontiers in Cell and Developmental Biology, 2017)
The mammalian cerebral neocortex has a well-organized laminar structure, achieved by the highly coordinated control of neuronal migration. During cortical development, excitatory neurons born near the lateral ventricle migrate radially to reach their final positions to form the cortical plate. During this process, dynamic changes are observed in the morphologies and migration modes, including multipolar migration, locomotion and terminal translocation, of the newborn neurons. Disruption of these migration processes can result in neuronal disorders such as lissencephaly and periventricular heterotopia. The extracellular protein, Reelin, mainly secreted by the Cajal-Retzius neurons in the marginal zone, plays a crucial role in the neuronal migration and neocortical lamination. Reelin signaling, which exerts essential roles in the formation of the layered neocortex, is triggered by the binding of Reelin to its receptors, ApoER2 and VLDLR, followed by phosphorylation of the Dab1 adaptor protein. Accumulating evidence suggests that Reelin signaling controls multiple steps of neuronal migration, including the transition from multipolar to bipolar neurons, terminal translocation, and termination of migration beneath the marginal zone. In addition, it has been shown that ectopically expressed Reelin can cause neuronal aggregation via an N-cadherin-mediated manner. This review attempts to summarize our knowledge of the roles played by Reelin in neuronal migration and the underlying mechanisms.